Universitas Muhammadiyah Malang, Indonesia. - Subrata, Puthut Azis; Pratama, Abdulrokhman; Fajar, Teuku Indra; Nuphanudin (International Journal of Psychosocial Rehabilitation, 2020)
--A corruption-free of Indonesia is a big challenge for all the people in Indonesia. The characteristics of corruption in Indonesia are so complex and entrenched in order that the efforts to eradicate corruption are systematic, integrated and focused. This article offers an Anti-Corruption Model that combines all anti-corruption programs so that the governance process can run transparently and accountably to achieve an Indonesia that has legal certainty, sustainable development and quality of life. This article was written using the meta-analysis method. This is done by reviewing previous research and studying various relevant literature. Then, an in-depth analysis of empirical facts combined with a comprehensive literature review results in Anti- Corruption Model 1:99. Anti-Corruption Model 1: 99 is an answer to the challenge in create a corruption-free Indonesia. This model covers all aspects of needs and covers every aspect of community life. In the end, the synergy and integration of all components anti-corruption innovation in the community. It can be executed so that it is realized in the form of concrete actions.Key words--,  ,